Poly(aryleneethynylene) tongue that identifies nonsteroidal anti-inflammatory drugs in water: a test case for combating counterfeit drugs - Han, Jinsong; Wang, Benhua; Bender, Markus; Kushida, Soh; Seehafer, Kai; Bunz, Uwe H. F. (ACS applied materials & interfaces, 2017)
We report a sensor array composed of a highly ﬂuorescent positively charged poly(para-phenyleneethynylene) P1 and its complex C with a negatively charged pyridine-containing poly(para-aryleneethynylene) P2 (quencher) at pH 10 and pH 13; a sensor ﬁeld composed of four elements, P1 (pH 10), P1 (pH 13), C (pH 10), and C (pH 13), results. The elements of this small sensor ﬁeld experience either ﬂuorescence turn on or ﬂuorescence quenching upon exposure toward nonsteroidal anti-inﬂammatory drugs (NSAIDs), such as aspirin, ibuprofen, diclofenac, or naproxen. The combined responses of the sensor ﬁeld are analyzed by linear discriminant analysis (LDA). All of the NSAIDs were identiﬁed and discriminated, and the sensing mechanism, hydrophobic versus electrostatic, was discussed.
Published December 16, 2016
Gesehen am 05.07.2018